Design of a model of management for the development of the small agricultural rural units of Peru asociatividad’s workshops - Chong Chong, Mario (2012)
One of the main problems faced by small rural farming units is to develop and implement managerial models that contribute to leverage their natural potential and boost their productive development. In order to mitigate the impact of this problem, a cross-section, exploratorydescriptive, non-experimental and prospective research was carried on, between 2008 and 2011. The main propose of this research was to design a model for autonomous development which integrates the public, private and academic sectors in order to ensure the use of the resources in a sustainable and competitive manner taking into account agricultural practices, water resources, technological park, non-traditional activities (tourism and aquaculture ) and government public policies.